1998
DOI: 10.1046/j.1471-4159.1998.71020478.x
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional and Posttranscriptional Control of Tyrosine Hydroxylase Gene Expression During Persistent Stimulation of Pituitary Adenylate Cyclase‐Activating Polypeptide Receptors on PC12 Cells: Regulation by Protein Kinase A‐Dependent and Protein Kinase A‐Independent Pathways

Abstract: Abbreviations used: cAMP, cyclic AMP; PACAP, pituitary adenylate cyclase-activating polypeptide; PKA, protein kinase A, the cyclic AMP-dependent protein kinase; PKC, protein kinase C; TH, tyrosine hydroxylase; VIP, vasoactive intestinal polypeptide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 51 publications
1
23
0
Order By: Relevance
“…The PC12 cell line has been widely used to investigate the various effects of PACAP on neuronal differentiation including neuritogenesis (Deutsch and Sun, 1992;Lazarovici et al, 1998), inhibition of cell division (Deutsch and Sun, 1992), stimulation of expression of neuroendocrine-specific genes such as neuropeptide Y and tyrosine hydroxylase (Corbitt et al, 1998) and changes in electrical excitability and secretion Fig. 9.…”
Section: Discussionmentioning
confidence: 99%
“…The PC12 cell line has been widely used to investigate the various effects of PACAP on neuronal differentiation including neuritogenesis (Deutsch and Sun, 1992;Lazarovici et al, 1998), inhibition of cell division (Deutsch and Sun, 1992), stimulation of expression of neuroendocrine-specific genes such as neuropeptide Y and tyrosine hydroxylase (Corbitt et al, 1998) and changes in electrical excitability and secretion Fig. 9.…”
Section: Discussionmentioning
confidence: 99%
“…7). Interestingly, PACAP exerts a persistent post-transcriptional effect on the steady-state levels of tyrosine hydroxylase in PC12 cells (Corbitt et al, 1998).…”
Section: Tight Regulation Of Otp During Hypothalamic Developmentmentioning
confidence: 98%
“…Finally, it has recently been reported that the neuroprotective effect of nicotine on differentiated PC12 cells could involve PACAP expression (Tominaga et al, 2008). Besides its effects on PC12 cell differentiation and survival, PACAP has been shown to stimulate catecholamine secretion, to induce cell excitability, and to enhance the biosynthesis of other neuropeptides in PC12 cells (Corbitt et al, 1998;Grumolato et al, 2003b;Ravni et al, 2006b). The PACAP-evoked increase in TH expression is regulated through both the PKA and PKC pathways (Corbitt et al, 2002).…”
Section: Effects Of Pituitary Adenylate Cyclase-activating Polypepmentioning
confidence: 99%